Validation of the Malay Version of the COVID-19 Anxiety Scale in Malaysia - Chin Siang, Ang; Kai Wee, Lee; Meng Chuan, Ho; Siok Ping, Voon; Siew Mooi, Ching; Chai Eng, Tan; Fan Kee, Hoo; Pei Boon, Ooi (Penerbit Universiti Sains Malaysia, 2022)
Background: Malaysians are disillusioned with the increased number of COVID-19 infection cases and the prolonged lockdown period. As a result of COVID-19 mitigation measurements, Malaysians are experiencing emotional and psychological consequences such as anxiety. Thus, there is an urgent need to have an instrument that could serve as a tool to assess the psychological impact of COVID-19 among Malaysians rapidly. Methods: This study aimed to adapt and validate the Malay version of the COVID-19 Anxiety Scale (M-CAS) among Malaysian adults. The back-to-back translation was done to produce a M-CAS. Following face validation, M-CAS was self-administered to 225 participants from Malaysia via an online survey. The participants also completed the Generalised Anxiety Disorder 7-item Scale (GAD-7), World Health Organization Quality of Life Scale, Abbreviated Version (WHOQOL-BREF) and the Fear of COVID-19 Scale (FCV-19S). Data analysis was conducted using Statistical Package for the Social Sciences and Analysis of a Moment Structures. The psychometric properties of the M-CAS were examined via Cronbach alpha and confrmatory factor analysis. M-CAS scores were compared with the other tools to provide external validity. Results: The statistical analysis revealed that the M-CAS demonstrated adequate internal consistency (Cronbach’s alpha = 0.890) and presented with a unidimensional factor structure. M-CAS scores were strongly correlated with GAD-7 (r = 0.511, P < 0.001) and FCV-19S (r = 0.652, P < 0.001). Lack of correlation between M-CAS and WHOQOL-BREF showed that M-CAS scores did not reﬂect perceived quality of life. Conclusion: The M-CAS is a valid and reliable tool in the Malay language that can be selfadministered among Malaysians to assess anxiety levels induced by COVID-19. The M-CAS has only 7 items and utilised little time in real-life clinical practice.